Experimental Assessment of Wind Loads on Vinyl Wall Siding - Moravej, Mohammadtaghi; Zisis, Ioannis; Chowdhury, Arindam Gan; Irwin, Peter; Hajra, Bodhisatta (Frontiers in Built Environment, 2016)
Wind-induced damage to multi-layer building wall systems, such as systems with vinyl siding, is common, especially in hurricane-prone areas. Wind load distribution through these multi layered walls and the amount of load reduction due to pressure equalization is expressed through Pressure Equalization Factors (PEF). The ASTM D3679 standard suggests a PEF of 0.36, which means a 64% reduction in the net pressure on the siding. This paper presents results from an experimental study conducted on a low-rise building subjected to realistic wind loading conditions at the Wall of Wind (WOW) experimental facility at Florida International University (FIU). Results from area averaged mean and peak pressure coefficients indicated that a very small portion of the total wind load is carried by the vinyl siding. However, PEF’s were found to be much higher when individual taps were considered. For instance, PEFs ranged from 71% to 106% for the case of pressure coefficients with negative sign (suction) and 39% to 110% for the case of pressure coefficients with positive sign (pressure). When a combined set of taps was considered, PEFs ranged approximately from 50% to 80% for the case of ‘suction’ and 15% to 75% for ‘pressure’. Based on the 1 m2 of tributary area used in ASCE 7-10 Standard, results show that the net load on vinyl wall siding can be obtained by reducing the net design load for the entire wall assembly by 25% and 60% for suctions and pressures, respectively. However, a smaller tributary area (< 1 m2) can experience a local peak load that can induce damage to connections, especially in the case of relatively flexible wall coverings, with no or very little load sharing between connection points. Results indicate that for smaller areas (~ 0.2 m2) the allowable percentage reductions should not be more than 15% and 25% for suctions and pressures, respectively. This study shows that the suggested ASTM PEF of 0.36 may lead to the underestimation of loads for the design of details affected by local loads. However, further research is needed to consider more cases when developing adequate design load guidelines for vinyl wall sidings.